Variation and linkage disequilibrium between a structurally polymorphic Alu located near the OR12D2 gene of the extended major histocompatibility complex class I region and HLA‐A alleles. (5th December 2013) - Kulski, J. K.; Shigenari, A.; Inoko, H.
Summary We investigated the genetic structure and population frequency of an Alu repeat dimorphism (absence or presence) located near the OR12D2 gene within the olfactory receptor gene region telomeric of the alpha HLA class I region (HLA‐J, ‐A, ‐G, ‐F). The structurally polymorphic Alu insertion (POALIN) locus rs33972478 that we designated as AluOR and its allele and haplotype frequencies and association with HLA‐A and six other structurally polymorphic retroelements (3 Alu, 2 SVA and an HERVK9) were determined in 100 Japanese, 174 Caucasians and 100 African American DNA samples. The AluOR insertion varied in population frequency between 14.4% and 31.5% with significant differences between the Japanese and Caucasians, but not between the Caucasian and African Americans. Although AluOR is located 600 kb from the HLA‐A gene, there was a significant linkage disequilibrium between the two loci and a high percentage association of the AluOR insertion with HLA‐A29 (79%) in Caucasians and HLA‐A31 (69.4%) in Japanese. Inferred haplotypes among three‐locus to eight‐locus haplotype structures showed maximum differences between the populations with the eight‐locus haplotypes. The most frequent multilocus haplotype shared between the populations was the HLA‐A2 allele in combination with the AluHG insertion. The AluOR whether investigated alone or together with the HLA class I alleles and other dimorphic retroelements is an informative ancestral marker for the identification of lineages and variations within the same and/or different populations and for examining the linkage and crossing‐over between the HLA and OR genomic regions in the extended MHC.